Proceedings of the 18th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2015
DOI: 10.1145/2675133.2675176
|View full text |Cite
|
Sign up to set email alerts
|

Handheld or Handsfree?

Abstract: Emerging wearable and mobile communication technologies, such as lightweight head-mounted displays (HMDs) and handheld devices, promise support for everyday remote collaboration. Despite their potential for widespread use, their effectiveness as collaborative tools is unknown, particularly in physical tasks involving mobility. To better understand their impact on collaborative behaviors, perceptions, and performance, we conducted a two-by-two (technology type: HMD vs. tablet computer; task setting: static vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…in the moment. I also found that head-mounted displays offered no meaningful benefit in terms of making or using annotations, but consistent with prior work, facilitated feedback on the current actions be carried out (Johnson et. al., 2015).…”
Section: Chapter One: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…in the moment. I also found that head-mounted displays offered no meaningful benefit in terms of making or using annotations, but consistent with prior work, facilitated feedback on the current actions be carried out (Johnson et. al., 2015).…”
Section: Chapter One: Introductionsupporting
confidence: 77%
“…al., 1999, Gauglitz et. al., 2012, Johnson et al, 2015. One of the classic challenges in supporting remote collaboration is the need to reference objects or locations efficiently through video (Buxton 2009, Fussel et.…”
Section: Chapter One: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technological solutions for remote collaboration have taken many different forms. From letters, telephone, video-conference systems to more advanced forms of technology that are now starting to show potential for creating efficient and natural forms of collaboration [Celata et al 2018;Fussell et al 2003;Johnson et al 2015;Khan et al 2016;Piumsomboon et al 2016]. However, most of these authors also claim that the lack of developed technology can hinder good collaboration.…”
Section: Related Workmentioning
confidence: 99%
“…3.2.9 Asymmetric user interface. It has been shown that by making use of specialized roles, as well as the knowledge-in-common of participants, collaboration can turn out to be more effective [Carroll et al 2006;Johnson et al 2015]. As such, similarly to [Elvezio et al 2018], we adopt an asymmetric user interface where we emphasize how certain users can be specialized in certain tasks.…”
Section: Animating Camerasmentioning
confidence: 99%